Monitoring of Certain Serum biochemical Parameters DuringTransition Period in Camels (Camelus dromedarius) - Elkhair, Nawal M.; Ahmed, Mona H.; Alameen, Ahmed O. (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of the study was to monitor certain electrolytes, serum proteins and certain acid-base parameters during the transition period in camels. Twenty multiparous females (pregnant and non-pregnant, age: 7-11year, number of parities: 2-3) of Arabi breed were used. Jugular venous blood was collected three times: one month prepartum, at parturition and one month postpartum and once from non-pregnant females to determine blood pH, Na+, K+, Cl-, Pi, total proteins (TP) and albumin. Strong ion difference (SID3) and the total concentration of non-volatile weak acids (Atot) were calculated using validated equations. Serum- [Na+], [Cl-] and [TP] decreased significantly (P<0.0001) during the transition period while [Pi] and [albumin] increased (P≤0.05). Serum-[SID3] and [Atot] tended to increase and decrease on-significantly, respectively. During late pregnancy,[K+] was correlated negatively and positively (P<0.05) to [Cl-] and [albumin] while [albumin] and [Pi] was correlated positively (P=0.02) in non-pregnant camels. During postpartum period, [Na+] and [Cl-]; [TP] and [albumin] were correlated positively (P≤0.05). Serum-[SID3] and [Atot]showed linear relationship (P<0.0001, R2 = 0.55-0.99) to [Cl-], [Pi] and [albumin] during the transition period and in non-pregnant camels. The transition period has an influence on certain serum electrolyte concentration, serum proteins and certain acid-base parameters. The data could be utilized for the clinical monitoring of metabolic disorders associated with transition period or to formulate dietary ratios to meet the nutritional requirement during these critical periods.